Relaxin regulates vascular wall remodeling and passive mechanical properties in mice - Debrah, Dan O. (American Physiological Society, 2011)
Administration of recombinant human relaxin (rhRLX) to conscious rats increases global arterial compliance, and small renal arteries (SRA) isolated from these rats demonstrate increased passive compliance. Here we characterize relaxin-induced vascular remodeling and examine its functional relevance. SRA and external iliac arteries (EIA) were examined in rhRLX-treated (1.0 μg/h for 5 days) and relaxin knockout mice. Arterial geometric remodeling and compositional remodeling were quantified using immunohistochemical and biochemical techniques. Vascular mechanical properties were quantified using an ex vivo preparation wherein pressure-diameter data were obtained at various axial lengths. Compared with vehicle-treated mice, SRA from rhRLX-treated mice showed outward geometric remodeling (increased unstressed wall area and wall-to-lumen area ratio), increased smooth muscle cell (SMC) density, reduction in collagen-to-total protein ratio, and unchanged elastin-to-tissue dry weight ratio. Compared with wild-type mice, relaxin knockout mice exhibited the opposite pattern: decreased unstressed wall area and wall-to-lumen area ratio, decreased SMC density, and increased collagen-to-total protein ratio. Although tissue biaxial strain energy of SRA was not different between rhRLX- and vehicle-treated groups at low-to-physiological circumferential and axial strains, it was lower for the rhRLX-treated group at the highest circumferential strain. In contrast to SRA, relaxin administration was not associated with any vascular remodeling or changes in passive mechanics of EIA. Thus relaxin induces both geometric and compositional remodeling in vessel-specific manner. Relaxin-induced geometric remodeling of SRA is responsible for the increase in passive compliance under low-to-physiological levels of circumferential and axial strains, and compositional remodeling becomes functionally relevant only under high circumferential strain.